The clauses SMM2 at construction site board game for (WBLFF) / Roseline Ikau ... [et al.] - Ikau, Roseline; Bidin, Zafikha Aida; Amat Rais, Syamimi Liyana; Adnan, Amira Shazlin; Othman, Mohd Khairul Fitri (2021)
The development of the Clauses Smm2 at Constructıon Sıte Board Game for (WBLFF) is as a platform to offer the new built environment students the overview of the proses taking off quantities for construction of works. Quantities of materials are materials that are measured in accordance with the Standard Method of Measurement of Building Works (SMM). This interactive game fulfils the syllabus related to construction courses of Measurement of Construction Works. Basically this game focuses on the knowledge of the elements of Work Below Lower Floor Finishes (WBLFF) which provides the information on the processes involved in the preparation of taking off quantities for element WBLLF from excavation of topsoil until the concrete works for ground slab. Taking off is taking the dimensions from architectural or structural drawings and entering the dimension with appropriate descriptions on taking off papers. It is well known that students have difficulty with theory related understanding, especially for the period of long discussions in lectures. As a result, the students will often fail to remember the information delivered during the lecture. The Clauses Smm2 at Constructıon Sıte Board Game for (WBLFF) which is consists of sixteen (16) major clauses developed from Malaysian Standard Method of Measurement of Building Works Second Edition from Excavation and Earthwork in Section D to Waterproofing and Asphalt work in Section K. The application of this game in a classroom provides a more conducive method for the students to improve their understanding of the steps taking off quantities for element Work Below Lower Floor Finishes (WBLFF) according to Malaysian Standard Method of Measurement of Building Works Second Edition (SMM2). This board game suitable for a tutorial session with supervision by the lecturers. Through games, students are more motivated to learn, thus, improve their attention in class. Even more, this game serves as an indicator for the lecturer to verify the level of understanding of the students on the taking off quantities in measurement of construction knowledge.